Trends in childhood vaccinations coverage in Lombardy Region after the National Vaccine Prevention Plan (2017-19) and the new law on mandatory vaccinations - Croci, Roberto; Rossi, Deanna; Colucci, Maria Eugenia; Odone, Anna; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2020)
In Italy, over the last decade, the spread of vaccine hesitancy has caused a steep decrease in vaccination coverage rates, both at the national and regional level. In this study, we pool and critically analyze childhood immunization coverage rates (2011-2018) in Lombardy, Italy’s most populated region, and compare them to national trends. Overall, childhood vaccination coverage in Lombardy is slightly higher the Italian national average. In 2017, the law on mandatory vaccinations came into force, acting as a powerful tool for coverage increase.